New values for cut set catalan numbers - Dochkova, Juliana,; Krone, Martin,; Mengersen, Ingri, (Utilitas Mathematica, 2013)
With the aid of a computer using improved methods the values of the cut set Catalan numbers Sn are determined for 26 ≤ n ≤ 29.